REPRESENTASI GENERASI MILENIAL DALAM IKLAN AXE MEN'S GROOMING DI MEDIA YOUTUBE : Analisis Semiotika Roland Barthes - Sya Bagussalam Ariyanto, I'al (2020)
Millennial generation is now becoming a concern. Nowadays, millennials are in their productive age and could impact a major influence on world development. Regarding the popular phenomenon of millennial generation, AXE presents an advertisement for their Men 's Grooming product series with a style that represents millennial generation, starting from the selection of the cast, the behavior displayed, to the style of fashion and background decoration. This is considered as a fresh movement for AXE, because previous product advertisements are only dominated by sensuality and masculinity. This study aims to determine the representation of millennial generation in YouTube AXE Men's Grooming ads. This research was analyzed using Roland Barthes' semiotic analysis theory to find out the meaning of denotation, connotation, and myth in the advertisement. While the method used is a qualitative method that is interpretive, explaining the detail using the text of the existing signs. This research will produce denotation, connotation, and myths meaning that contained in YouTube AXE Men's Grooming advertisement. The conclusion of this research is, this ads represents millennial generation, including style and behavior that contain denotation, connotation, and myths. Suggestions for advertisers is to be sensitive to the phenomena in society to make more creative advertising ideas.